Deep Breathing Exercise on the Anxiety Level of Tuberculosis Patients in Dau District - Rahmawati, Nurul Aini; A'yun, Az Zahra Qurrota; Ma'rufah, Siti Ainun (Sarana Ilmu Indonesia (salnesia), 2024)
Tuberculosis poses a serious problem that requires regular and long-term treatment.. This can cause psychological problems such as anxiety, stress, and even depression in sufferers. Therefore, this study aimed to determine the effect of deep breathing exercise on the anxiety level of tuberculosis patients in Dau District. The type of research method used was Quasi Experimental using the One Group Pre and Post Test method which was carried out at the Dau District Health Center in March-April 2023 with a total subject of 25 TB patients. The instrument used was the HARS questionnaire. Results of statistical tests contained in the table there was p-value= 0,000. So that, Deep Breathing Exercise provides a significant influence on the golden level of patients with Pulmonary TB. Based on the results of the research conducted, it can be concluded that deep breathing exercise can be one of the complementary therapy options to overcome anxiety problems in patients with pulmonary TB undergoing treatment.